Consumer behavior: digital lifestyle / Muhammad Hanif Abdul Gafar and Nor Amira Mohd Ali - Abdul Gafar, Muhammad Hanif; Mohd Ali, Nor Amira (Universiti Teknologi MARA, Kedah, 2023)
Technologies have indeed changed the consumer’s approach to life, and it is a vital factor in the macro environment in the marketing platform to control manufacturers and service providers. Most of the key players in businesses have moved forward as far as they can to bring advanced technology into their routine activities, especially when dealing with consumers. Advanced technology will make lives easier because all the daily transactions and activities can be done at their fingertips. Due to the pandemic for the last two years, most businesses have shifted their transaction and business activities online, and consumers have changed their buying habits. To date, consumer behavior trends have accelerated towards a digital lifestyle. Four essential fault lines have emerged that separate global consumers into distinct cohorts (how consumers shop, travel, work and engage with brands). Thus, it will have implications for consumer market industries, and of course, business organizations need to understand these emerging cohorts to deliver and fulfill the consumer’s needs and preferences.